Digital preservation of Zhujiayu Village’s cultural landscape: a new approach to sustainable development / Wang Tongyun ... [et al.] - Tongyun, Wang; Ghani, Izham; Ahmad, Suriati; Abdul Rahman, Norhafizah; Shiwan, Zhou; Wahid, Hairunkamal (UiTM Press, 2024)
This paper examines Zhujiayu Village in China, focusing on its distinctive natural environment, traditional architecture, and intangible cultural heritage. By integrating digital preservation with sustainable development, the study aims to safeguard and perpetuate the unique cultural landscape of Zhujiayu Village. At the core of this study is the application of digital technology in the conservation of cultural landscapes by employing technologies such as 3D scanning, geographic information systems (GIS), and virtual reality (VR) to create a comprehensive digital archive of the village's traditional architecture, cultural landscapes, and intangible heritage. Through the creation of digital archives, a detailed record will be provided for the restoration projects of future buildings while raising public awareness of the protection of buildings and intangible cultural heritage. Through the construction of digital scenes, virtual tourism is promoted so that more people can understand the culture of Zhujiayu Village and reduce the wear and tear of intangible cultural heritage. The study also explores the challenges and opportunities of digital protection technologies, highlighting the need for collaborative efforts between government agencies, local communities, and tourism management organisations. In conclusion, the Zhujiayu Village Cultural Landscape digital conservation study model not only provides a pioneering approach to heritage conservation but also provides valuable insights and a framework that can be adapted and applied to other similar rural cultural heritage conservation in China, marking an important step towards the sustainable development of heritage conservation.